Pré-tratamento do bagaço de cana-de-açúcar, hidrólise e sua caracterização química e estrutural, visando a produção de etanol de segunda geração - Roldan, Ismael Ulises Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The fermentation of sugarcane bagasse hydrolyzate (BCA) allows obtaining ethanol 2G. One of the main challenges in this work was to develop methodologies for obtaining rich hydrolysates into glucose for fermentation. Seven pretreatments BCA resulted from simplifications and adjustments based on literature procedures were carried out with the goal of getting rich fractions from pretreatment most appropriate in converting cellulose into fermentable sugars into ethanol. Techniques of chemical, morphological and structural characterization were applied to sugarcane bagasse and cellulose-enriched fractions were submitted the various pretreatments in order to predict and compare it. These techniques were SEM, FT-IR, XRD, TG and chemical analysis using the TAPPI method. The pre- treatment based on the use of sodium hydroxide assisted by microwave proved to be more efficient and this has resulted in fractions rich in cellulose PT6. Concentrations of total phenols and furans resulting from acid extractions applied to cellulose-enriched fractions were also determined. The highest concentrations of phenol extractions were obtained for fractions rich in cellulose using 30% (w/v) sulfuric acid in the presence of 100 mM FeCl3, whereas solutions of sulfuric acid, both total phenols as furans were obtained at lower concentrations possibly due to degradation. However, the use of 30 % (w/v) sulfuric acid was not recommended for extracting minor fractions of other concentrations. Finally, the best pretreatment resulted in a fraction PT6 for its higher performance and lower loss of the initial mass of the BCA, whereas treatment with 6% (w/v) sulfuric acid in the presence of 100 mM FeCl3 total reducing sugars released more non- solubilized during the pretreatment . This seems the most promising enriched fractions of cellulose for obtaining second-generation ethanol.

A fermentação do hidrolisado de bagaço de cana-de-açúcar (BCA), permite a obtenção de etanol 2G. Um dos principais desafios neste trabalho foi desenvolver metodologias para obtenção de hidrolisados ricos em glicose para a fermentação. Sete pré-tratamentos do BCA resultaram de simplificações e ajustes com base em procedimentos descritos na literatura foram realizados com o objetivo de obter frações ricas de pré-tratamento mais adequado na conversão de celulose em açúcares fermentáveis em etanol. Técnicas de caracterização química, morfológica e estrutural foram aplicadas ao bagaço de cana e frações ricas com celulose foram apresentadas aos vários pré-tratamentos a fim de prever e compará-los. Estas técnicas foram SEM, FT-IR, DRX, TG e análise química, utilizando o método TAPPI. O pré-tratamento com base na utilização de hidróxido de sódio assistida por microondas provou ser mais eficiente e isto resultou em fracções ricas em celulose PT6. As concentrações de fenóis totais e furanos resultantes de extrações ácidas aplicadas a frações ricas com celulose também foram determinados. As concentrações mais elevadas de extrações com fenol foram obtidos para as frações ricas em celulose, utilizando 30 % (m/v) de ácido sulfúrico, na presença de 100 mM de FeCl3, enquanto que as soluções de ácido sulfúrico, ambos os fenóis como os furanos foram obtidos em concentrações mais baixas, possivelmente devido degradação. No entanto, a utilização de 30 % (m/v) de ácido sulfúrico não era recomendada para a extração de frações menores de outras concentrações. Finalmente, o melhor pré-tratamento resultou no PT6 por seu maior rendimento e menor perda de massa inicial do BCA, enquanto que o tratamento com 6 % (m/v) de ácido sulfúrico, na presença de 100 mM de FeCl3 liberou mais açúcares redutores libertados mais não-solubilizado durante os...
Keywords: Biotecnologia; Bagaço de cana; Hidrolise; Viscosidade; Termogravimetria; Hydrolysis